2019
DOI: 10.1186/s40813-018-0113-6
|View full text |Cite
|
Sign up to set email alerts
|

Using the Biocheck.UGent™ scoring tool in Irish farrow-to-finish pig farms: assessing biosecurity and its relation to productive performance

Abstract: Background Biosecurity is one of the main factors affecting disease occurrence and antimicrobial use, and it is associated with performance in pig production. However, the importance of specific measures could vary depending on the (national) context. The aim of this study was to describe the biosecurity status in a cohort of Irish pig farms, to investigate which of those biosecurity aspects are more relevant by using the Biocheck.UGent™ scoring system, and to study the impact of such aspects on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 16 publications
3
30
2
Order By: Relevance
“…However, recent work has identified respiratory disease as a significant problem on Irish pig farms [56] and this may explain the high use of antimicrobials in the weaner diets fed to 2nd stage weaner pigs. Also, internal biosecurity on Irish pig farms is lower than in other European countries [57]. Improved biosecurity was shown to aid in reducing AMU on Belgian pig farms [58] and a recent initiative launched by Animal Health Ireland has made biosecurity audits available to all Irish pig farms.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has identified respiratory disease as a significant problem on Irish pig farms [56] and this may explain the high use of antimicrobials in the weaner diets fed to 2nd stage weaner pigs. Also, internal biosecurity on Irish pig farms is lower than in other European countries [57]. Improved biosecurity was shown to aid in reducing AMU on Belgian pig farms [58] and a recent initiative launched by Animal Health Ireland has made biosecurity audits available to all Irish pig farms.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement gilts were home-reared as per common practice in Irish pig farms (32); selected at 24 weeks of age and artificially inseminated at their second oestrous. All breeding females were artificially inseminated when standing oestrous was observed and 24 h after the first service.…”
Section: Simulated Farmmentioning
confidence: 99%
“…For example, 85.7% of unvacPRRSv(+) farms always isolated sick pigs and consistently handled them after healthy ones (Calderón Díaz et al, in preparation) compared with 61% of vacPRRSv(+) farms practicing the same measures as per results from the Biocheck.UGent TM (https://www.biocheck.ugent.be/ index.php?) scoring tool completed as part of the crosssectional study conducted by Rodrigues da Costa et al (32). Additionally, unvacPRRSv(+) farms higher score for disease management than vacPRRSv(+) farms (90.0 ± 21.07 vs. 73.3 ± 20.49, respectively; Calderón Díaz et al, in preparation).…”
Section: Porcine Reproductive and Respiratory Syndrome Virusmentioning
confidence: 99%
“…Therefore, high scores reaching the maximum score of 100% can be more easily obtained for internal biosecurity. Costa et al (2019) researched the effect of biosecurity scores and farm characteristics on productive performance. They found that there was an increase in mortality with age of the youngest building in which pigs were kept, and a tendency for it to decrease in farms with better scores in the biosecurity category referring to feed, water, and equipment supply.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%